Peran Lembaga Alkitab Indonesia Dalam Preservasi Dan Diseminasi Kitab Suci - Abdullah Muslich Rizal Maulana; Fadhillah Rachmawati; Adelia Elmira Mayda Firmansyah; Rika Yua Prasetya; Fadhillatuz Zahroh Putri; Aqila, Hana Juhaida (International Forum of Researchers and Lecturers, 2024)
The Indonesian Bible Institute can be abbreviated as LAI. LAI has taken part in all Christian congregations by collaborating with the Bible. Which struggles to translate the entire Bible into the archipelago according to its regional language. Furthermore, LAI over time published after being translated and distributed to remote areas. With various developments in the journey of Bible translation, it involves a lot of history and covers various languages, cultures, and social contexts, making the Bible central in the lives of Christians around the world. This study uses qualitative research with direct observation at the LAI headquarters in Jakarta. The headquarters shows the preservation and dissemination of the Bible that has been hundreds of years from old events to new events. In conclusion, LAI has many strategies for development in preserving manuscripts so that they can still be read and available for future generations.